Morphostructural Development of Gunungsewu Karst, Jawa Island - Tjia, H. D. (Indonesian Journal on Geoscience, 2013)
DOI:Â 10.17014/ijog.v8i2.157Gunungsewu Karst (also known as Sewu karst in the literature) is synonymous with morphology of a carbonate terrain dominated by hills crowned by accordant-level tops that developed in a humid tropical environment by comparatively more rapid dissolution and denudation. In addition, the hills are sinoid to cone-shaped. Surface drainage is negligible compared to subsurface water flow. Abandoned channel segments and spatial arrangements of karst hills have been found to correspond with fracture patterns that are genetically associated with the regional compression direction of Jawa Island. Images derived from space platforms show many landform patterns that were neither known from ground-based nor from aerial photograph study. Landforms arranged in ring, multi-ring, spiral, polygonal, and long linear to serpentine patterns are common beside the expected depressions of dolines, poljes, and uvalas. The orientations of the long linear ridges appear to change systematically from those near the coast to those located inland. These linear ridges are interpreted as depositional fronts, most likely representing breaker zones. The youngest depositional ridge fronts, located nearest to the present shoreline, are parallel to the geological strike of Jawa Island. Toward the islandâs interior, linear depositional fronts deviate in orientation by as much as 40o. This is now interpreted to have resulted from counterclockwise rotation of the Gunungsewu microplate since the late Middle Miocene. Similar CCW rotations are indicated by the paleomagnetic orientations of igneous rocks located farther east in the southern range of the island. Active tectonics is expressed in stage-wise net uplift of Gunungsewu whereas regional tilting appears negligible. Stacked and often paired river terraces (thus suggesting land uplift) have been used to relatively date paleoarcheological finds. Very recent uplift on the coast show up in lazy-V limestone notch profiles, and occasionally by stacked notches. At the Klayar coast, slight northward tilt of a few degrees are expressed as counter-regional inclination of a subrecent abrasion platform.